Тhe bunch formation and transport system to the target of the helium ions linac - Dyachenko, A.F.; Anokhin, R.A.; Dubniuk, S.N.; Коbets, А.P.; Kravchenko, A.I.; Manuilenko, O.V; Reshetnikov, V.M.; Soshenkо, V.A.; Tishkin, S.S.; Zajtsev, B.V.; Zhuravlоv, O.V.; Zhuravlоv, V.G. (Вопросы атомной науки и техники, 2018)
Ways of the bunch current and density increase at the target on the helium ions linear accelerator NSC “KhIPT” with output energy 4 MeV are considered. Possibility of its transportation with the minimum losses to target complex intended for carrying out of radiating researches is studied. Results of the researches spent on electromagnetic quadrupole lenses of a triplet are presented. Experiments with injected (120 кэВ) and accelerated (4 MeV) bunch of helium ions by means of bunch formation and transport system to a target are made.